2021
DOI: 10.3389/fevo.2021.664835
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Sequence Variations and SSR Marker Development in the Munake Grape Cultivar

Abstract: The Munake grape cultivar produces uniquely flavored and high-quality fruits. Despite the numerous beneficial agronomic traits of Munake, there are few genetic resources available for this cultivar. To address this knowledge gap, the entire genome was sequenced using whole-genome sequencing approaches and compared with a Vitis vinifera L. reference genome. This study describes more than 3 million single nucleotide polymorphism (SNP), 300,000 insertion and deletion (InDel), 14,000 structural variation (SV), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Some molecular markers are used within cabbage, like sequence-related amplified polymorphism (SRAP), universal random amplified polymorphic DNA (RAPD), restriction fragment length polymorphism and amplified fragment length polymorphism (AFLP) markers ( Ikten et al, 2019 ). Currently, informative molecular markers have emerged, which offer precious knowledge for genomic and genetic research on cabbage ( Gadaleta et al, 2012 ; Zhong et al, 2017 ). However, regardless of the development of SSR markers, those developed from cabbage reference genome are lacking compared with those in other crops.…”
Section: Introductionmentioning
confidence: 99%
“…Some molecular markers are used within cabbage, like sequence-related amplified polymorphism (SRAP), universal random amplified polymorphic DNA (RAPD), restriction fragment length polymorphism and amplified fragment length polymorphism (AFLP) markers ( Ikten et al, 2019 ). Currently, informative molecular markers have emerged, which offer precious knowledge for genomic and genetic research on cabbage ( Gadaleta et al, 2012 ; Zhong et al, 2017 ). However, regardless of the development of SSR markers, those developed from cabbage reference genome are lacking compared with those in other crops.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that WRKY gene family was probably high-conserved in different B. striata germplasms. These newly found SSR primers could be used as molecular markers to identify the members of BsWRKY gene families in different germplasm (Zhong et al, 2021).…”
Section: Est-ssr Polymorphism Of Wrky Genes In Different Germplasms O...mentioning
confidence: 99%
“…Dunlevy [54] analyzed the genotyping and sodium exclusion phenotype of grape hybrid populations ("K51-40 "×" Schwarzmann") based on SSR characteristics in the genome. Zhong [55] identified sequence variation and developed SSR markers across the whole genome of the Munake Grape Cultivar. Although RNA-seq technology has made great progress in recent years, the largescale development of specific SSR markers for miRNA in grapes has not been reported.…”
Section: Development and Application Of Mirna-ssr Markersmentioning
confidence: 99%